La valutazione del tutorato formativo per gli studenti universitari Il processo, la soddisfazione, l'efficacia - Clerici, Renata (Universitá: Didattica, Valutazione, Professionalitá docente/University: Teaching, Assessment and Professional Development - Open, 2019)
The text presents the evaluation model of an experimental program of extracurricular activities aimed at preventing drop-outs and promoting the empowerment of new university students, through the development of transversal skills. The training tutoring program being evaluated was proposed in eight first level degree courses of the University of Padua.